ICT-Based Statistical Learning Design to Train Middle School Students Higher Order Thinking Skills - Wahana, Nadhilah Putri; Abadi, Abadi (FKIP Universitas Lampung, 2023)
Abstract: This research aims to develop a statistical learning design for ICT-based data presentation material to train HOTS skills for junior high school students using the Successive Approximation Model (SAM) development method. The research was conducted at a junior high school in the city of Surabaya with 33 class VIII students as research subjects. The assessment of the feasibility of the learning design was validated by 2 lecturers and 1 mathematics teacher. The validation results for the HOTS questions obtained an assessment result of 80.4% (feasible), the material received 80.9% (feasible), and the media 83.7% (very feasible) so that the design instrument could be declared suitable for use. The learning design used in the learning process got a result of 97.7% (very practical) in observing the implementation of learning and a result of 95.8% (very practical) in observing student activities. Based on these results, the learning design was practical to use. The learning process obtained student responses to learning tools showing 94% of students agreed that learning tools helped in the learning process, and student responses to ongoing learning activities showed 89.8% of students agreed that learning activities helped in understanding the material. The students' posttest results of 84.84% met the minimum standard score, because the results of student responses were positive and above 80% of students met the minimum standard score, learning was effective to use. Based on these results, it can be concluded that the learning design is valid, practical and effective to use. Keywords: high order thinking skill, information and communication technology, learning design. Abstrak: Penelitian ini bertujuan untuk mengembangkan desain pembelajaran statistika materi penyajian data berbasis ICT untuk melatih keterampilan HOTS siswa SMP dengan metode pengembangan Successive Approximation Model (SAM). Penelitian dilakukan di SMP yang ada di Kota Surabaya dengan subjek penelitian siswa kelas VIII sebanyak 33 siswa. Penilaian kelayakan desain pembelajaran divalidasi oleh 2 dosen dan 1 guru matematika. Hasil validasi soal HOTS mendapatkan hasil penilaian 80,4% (layak), materi mendapatkan 80,9% (layak), dan media 83,7% (sangat layak) sehingga instrument desain dapat dinyatakan layak untuk digunakan. Desain pembelajaran digunakan dalam proses belajar mendapatkan hasil 97,7% (sangat praktis) pada pengamatan keterlaksanaan pembelajaran dan hasil 95,8% (sangat praktis) pada pengamatan aktivitas siswa, berdasarkan hasil tersebut desain pembelajaran praktis untuk digunakan. Proses pembelajaran mendapatkan respon siswa terhadap perangkat pembelajaran menunjukkan 94% siswa setuju bahwa perangkat pembelajaran membantu dalam proses pembelajaran, serta respon siswa terhadap kegiatan pembelajaran yang berlangsung menunjukkan 89,8% siswa setuju bahwa kegiatan pembelajaran membantu dalam memahamkan materi. Hasil posttest siswa 84,84% memenuhi standart nilai minimum, karena hasil respon siswa prositif dan diatas 80% siswa memenuhi standart nilai minimum maka pembelajaran efektif untuk digunakan. Berdasarkan hasil tersebut dapat disimpulkan bahwa desain pembelajaran valid, praktis, dan efektif untuk digunakan. Kata kunci: keterampilan berpikir tingkat tinggi, teknologi informasi dan komunikasi, desain pembelajaran. DOI: http://dx.doi.org/10.23960/jpmipa/v24i4.pp742-752